Solving Quadratic Fractional Programming Problem - Sulaiman, Najmaddin; Nawkhass, Maher (International Journal of Applied Mathematical Research, 2013)
In this paper the fractional Quadratic objective programming problem (QFPP) with linear constraints, has been defined and developed. The special case for this problem was solved by using the Wolfe’s method and a modified simplex approach, by suggesting an algorithm for each method to solve the problem. The computer application for algorithms was tested on a number of numerical examples, consequently reliable results have been found.